The Implementation of Monday–Thursday Fasting on the Enhancement of Students’ Religiosity at Hidayatullah Islamic Boarding School - Rezsky Al-Muttaqin. S, La Ode Muh; Basri; Ridwan, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2025)
This study examines the role of Monday–Thursday fasting in enhancing the religiosity of students at Hidayatullah Islamic Boarding School. Fasting, a recommended sunnah practice in Islam, is not only viewed as an act of worship but also as a medium for instilling discipline, moral integrity, and spiritual awareness. The pesantren setting provides a unique context where routine religious practices can serve as instruments of character education, shaping students to be both knowledgeable and virtuous. The purpose of this research is to analyze how the practice of Monday–Thursday fasting contributes to the development of students’ spiritual awareness, self-control, and moral character. A qualitative descriptive approach was employed, using interviews with teachers and caregivers as the primary data source, supported by observation and documentation. The findings reveal that fasting fosters consistency in performing daily religious obligations, such as congregational prayers and Qur’an recitation, while also strengthening students’ patience, humility, and empathy. Teachers highlighted that fasting not only deepens students’ understanding of the meaning of worship but also helps them balance academic responsibilities with spiritual growth. Overall, the program is recognized as an effective character education strategy that aligns with the pesantren’s vision of nurturing a generation that is both intellectually competent and morally upright.